2022
DOI: 10.1038/s41586-022-04790-2
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the Dicer-2–R2D2 heterodimer bound to a small RNA duplex

Abstract: In flies, Argonaute2 (Ago2) and small interfering RNA (siRNA) form an RNA-induced silencing complex to repress viral transcripts1. The RNase III enzyme Dicer-2 associates with its partner protein R2D2 and cleaves long double-stranded RNAs to produce 21-nucleotide siRNA duplexes, which are then loaded into Ago2 in a defined orientation2–5. Here we report cryo-electron microscopy structures of the Dicer-2–R2D2 and Dicer-2–R2D2–siRNA complexes. R2D2 interacts with the helicase domain and the central linker of Dic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(42 citation statements)
references
References 53 publications
(63 reference statements)
2
34
0
Order By: Relevance
“…These include structures of Drosophila Dicer-2, Apo-hsDicer-TRBP complex, hsDicer-TRBP bound to pre-let-7 in a pre-cleavage state, and a cleavage-competent structure of Arabidopsis Dicer-like-protein 3 (DCL3) bound to pre-siRNA . In addition to these structures, new structures continue to be reported including six Drosophila Dicer-1–Loquacious-PB (Loqs-PB) complex structures, six Drosophila Dicer-2–Loqs-PD complex structures, and two Drosophila Dicer-2–R2D2 complex structures . The 14 Drosophila Dicer structures depict dmDicer-1 and dmDicer-2 both apo- and in complex with dsRNA spanning a variety of conformational states.…”
Section: Advances In Dicer Structural Studiesmentioning
confidence: 99%
See 4 more Smart Citations
“…These include structures of Drosophila Dicer-2, Apo-hsDicer-TRBP complex, hsDicer-TRBP bound to pre-let-7 in a pre-cleavage state, and a cleavage-competent structure of Arabidopsis Dicer-like-protein 3 (DCL3) bound to pre-siRNA . In addition to these structures, new structures continue to be reported including six Drosophila Dicer-1–Loquacious-PB (Loqs-PB) complex structures, six Drosophila Dicer-2–Loqs-PD complex structures, and two Drosophila Dicer-2–R2D2 complex structures . The 14 Drosophila Dicer structures depict dmDicer-1 and dmDicer-2 both apo- and in complex with dsRNA spanning a variety of conformational states.…”
Section: Advances In Dicer Structural Studiesmentioning
confidence: 99%
“…50,51,75−78 Additionally, separate structural studies of dmDicer-2 bound to R2D2 in complex with siRNA revealed structural information for a strand selection/transfer conformation (Figure 4). 53 Together, these structures depict a nearly complete stepwise mechanism for dmDicer-2 ATP-dependent activity. However, while these structures may suggest that we have learned all we can about dmDicer-2, a unique dmDicer-2 dimer which is not shown in Figure 4 was also determined, revealing that, in the absence of ATP, dmDicer-2 dimerizes to form an initial binding complex with dsRNA.…”
Section: Dicer-2 Reveal Stepwise Mechanismmentioning
confidence: 99%
See 3 more Smart Citations